The US rebalancing to Asia : Indonesia's maritime dilemma - Ristian Atriandi Supriyanto (2014)
Being located at the crossroads of Indian and Pacific Oceans might seem a geostrategic blessing for Indonesia. But it could be a strategic disaster in the event of a heightened Sino-US maritime competition.